Have You Seen it Before?

a n b n + 1 = ( a + b ) n 1 a^n-b^{n+1}=(a+b)^{n-1}

Given that a , b , n a, b, n are positive integers such that gcd ( a , b ) = 1 \gcd(a, b)=1 and n > 1 , n>1, find all solutions ( a , b , n ) (a, b, n) to the equation above and enter your answer as ( a + b + n ) . \sum (a+b+n).


Inspiration: [Russian Mathematical Olympiad, 1997]

For prime numbers p p and q , q, solve p 3 q 5 = ( p + q ) 2 . p^3-q^5=(p+q)^2.


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Kazem Sepehrinia
Jul 14, 2017

It is clear that a > b 1 a>b \ge 1 . Looking mod b b gives b a n 1 ( a 1 ) b \mid a^{n-1} (a-1) and since gcd ( a , b ) = 1 \gcd(a, b)=1 we get b a 1 b|a-1 and a = b c + 1 a=bc+1 for a positive integer c c . Looking mod a a gives a b 2 + 1 a \mid b^2+1 . Thus a b 2 + 1 a 0 a \mid b^2+1-a \ge 0 . Or a b 2 + 1 ( b c + 1 ) = b ( b c ) a \mid b^2+1-(bc+1)=b(b-c) and a b c a \mid b-c . But for b c > 0 b-c>0 we get b + 1 a b c b+1 \le a \le b-c , which is a contradiction. Hence b = c b=c and a = b 2 + 1 a=b^2+1 .

The equation becomes ( b 2 + 1 ) n b n + 1 = ( b 2 + b + 1 ) n 1 (b^2+1)^n-b^{n+1}=(b^2+b+1)^{n-1} Suppose that p p is a prime divisor of b 2 + b + 1 b^2+b+1 . Looking mod p p gives ( b ) n p b n + 1 ‎(-b)^n ‎‎\stackrel{‎p‎}{\equiv} b^{n+1} or b p ( 1 ) n ‎b ‎‎\stackrel{‎p‎}{\equiv} (-1)^n . For n n being odd, it follows that b + 1 p 0 ‎b+1 ‎‎\stackrel{‎p‎}{\equiv} 0 , which is impossible since gcd ( b + 1 , b 2 + b + 1 ) = 1 \gcd(b+1, b^2+b+1)=1 . Thus n n is even and p b 1 p| b-1 and p b 2 + b + 1 b ( b 1 ) = 2 b + 1 p ( 2 b + 1 ) 2 ( b 1 ) = 3 p \mid b^2+b+1-b(b-1)=2b+1 \\ p \mid (2b+1)-2(b-1)=3 So p = 3 p=3 is the only prime divisor of b 2 + b + 1 b^2+b+1 and b 2 + b + 1 = 3 k b^2+b+1=3^k for a positive integer k k .

We have ( 2 b + 1 ) 2 = 4 × 3 k 3 (2b+1)^2=4\times 3^k-3 . LHS of this equation is divisible by 9 9 , but for k > 1 k>1 RHS is not divisible by 9 9 . Thus k = 1 k=1 . It follows that b = 1 b=1 and a = 2 a=2 . Now, the original equation is 2 n 1 = 3 n 1 2^n-1=3^{n-1} . Its immediate that n = 2 n=2 .

Thus the only solution is ( a , b , n ) = ( 2 , 1 , 2 ) (a, b, n)=(2, 1, 2) and answer is 5 \boxed{5} .

@Kazem Sepehrinia Nice solution haa :)

Sheyda Tamuzi - 3 years, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...